Replacement of dilation and curettage/evacuation by manual vacuum aspiration and medical abortion, and the introduction of postabortion contraception in Pakistan. (30th March 2014) - Zaidi, Shahida; Yasmin, Haleema; Hassan, Lubna; Khakwani, Mehnaz; Sami, Shehla; Abbas, Tazeen
Abstract: Manual vacuum aspiration (MVA) and medical abortion were introduced to replace dilation and curettage/evacuation for incomplete abortions, and postabortion contraception was provided in 5 selected public hospitals in Pakistan. In the largest hospital, an Ipas MVA training center since 2007, MVA use reached 21% in 2008. After the International Federation of Gynecology and Obstetrics (FIGO) and UNFPA provided MVA kits, MVA use increased dramatically to 70% − 90% in 2010 − 2013. In 2 of the remaining 4 hospitals in which the Society of Obstetricians and Gynecologists of Pakistan trained doctors in May 2012 and January 2013, the target of having 50% of women managed by MVA and medical abortion (MA) was met; however, in the third hospital only 43% were treated with MVA and MA. In the fourth hospital, where misoprostol and electric vacuum aspiration use was 64% and 9%, respectively, before training, an MVA workshop introduced the technique. Postabortion contraception was provided to 9% − 29% of women, far below the target of 60%.